2003
DOI: 10.1021/jp034702x
|View full text |Cite
|
Sign up to set email alerts
|

Building Blocks of Eumelanin:  Relative Stability and Excitation Energies of Tautomers of 5,6-Dihydroxyindole and 5,6-Indolequinone

Abstract: Computation methods were used to examine the tautomerization equilibria for 5,6-dihydroxyindole (DHI, 2) and 5,6-indolequinone (IQ, 3). Relative energies were calculated at the B3LYP and PBE0 level of theory; solvent effects were modeled by using the CPCM method. Nine tautomers of 2 were examined. Our data showed that the generally accepted molecular structure of 2 corresponds to the most stable tautomer in both gas phase and aqueous solution. In aqueous solution, the quinone methide tautomer was the second mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
87
2
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(102 citation statements)
references
References 52 publications
(67 reference statements)
11
87
2
2
Order By: Relevance
“…Therefore we have also employed the ∆SCF method [33] to calculate the HOMO-LUMO gap. We have previously shown that equivalent results for DHI reproduce the trends found in time dependent DFT calculations [23]. In table IV we compare the HOMO-LUMO gap found from a simple interpretation of the Kohn-Sham eigenvalues with those found by the ∆SCF method.…”
Section: Resultsmentioning
confidence: 53%
See 1 more Smart Citation
“…Therefore we have also employed the ∆SCF method [33] to calculate the HOMO-LUMO gap. We have previously shown that equivalent results for DHI reproduce the trends found in time dependent DFT calculations [23]. In table IV we compare the HOMO-LUMO gap found from a simple interpretation of the Kohn-Sham eigenvalues with those found by the ∆SCF method.…”
Section: Resultsmentioning
confidence: 53%
“…Despite the widespread agreement that natural eumelanin contains both DHI and DHICA, previous quantum chemical studies [14,15,17,18,19,20,21,22,23] have only considered DHI. This is in part due to the greater chemical complexity of DHICA, but also in part due to assumption that the carboxylation of DHI does not play a significantly role in determining the properties eumelanin.…”
Section: Introductionmentioning
confidence: 99%
“…Relative calculated energies for selected tautomers of the indole and quinone are shown. [9] As mentioned earlier, the indole 1 in its reduced state is characterized by a marked facility for oxidation, particularly in solution, thus sharing a notorious intractability with reactive catechols. Most of the difficulties involved in the study of 5,6-dihydroxyindole chemistry, however, have been circumvented by the adoption of suitable catechol protection strategies, based mainly on acetylation and benzylation.…”
Section: Structure and Chemical Propertiesmentioning
confidence: 90%
“…[20][21][22][23] All these studies concurred to indicate that 1 exists exclusively in the catechol form, with other tautomers appearing to be destabilized both in the gas phase and in solution. [9] With regard to 5,6-indolequinone, in solution the oquinone is the most stable tautomer but in the gas phase the quinonemethide is close in energy, indicating that in the gas phase it might constitute up to 25 % of 5,6-indolequinone.…”
Section: Structure and Chemical Propertiesmentioning
confidence: 99%
“…Eumelanin is derived by oxidation of dihydroxyphenylalanine (dopa) via the Raper-Mason scheme, and pheomelanin is produced via a similar pathway when cysteine is present. 7 Whereas eumelanin is believed to be comprised of aggregates of indolic monomers dihydroxyindole (DHI), [also known as hydroquinone (HQ)], its partially oxidized form semiquinone (SQ), and its fully oxidized form indolequinone (IQ), 8,9 pheomelanin is understood to consist of benzothiazine intermediates.…”
Section: Introductionmentioning
confidence: 99%